Automated microfluidic sorting of mammalian cells labeled with magnetic microparticles for those that efficiently express and secrete a protein of interest. Issue 8 (6th June 2017) - Droz, Xuan; Harraghy, Niamh; Lançon, Etienne; Le Fourn, Valérie; Calabrese, David; Colombet, Thierry; Liechti, Pascal; Rida, Amar; Girod, Pierre‐Alain; Mermod, Nicolas
ABSTRACT: We developed a method for the fast sorting and selection of mammalian cells expressing and secreting a protein at high levels. This procedure relies on cell capture using an automated microfluidic device handling antibody‐coupled magnetic microparticles and on a timed release of the cells from the microparticles after capture. Using clinically compatible materials and procedures, we show that this approach is able to discriminate between cells that truly secrete high amounts of a protein from those that just display it at high levels on their surface without properly releasing it. When coupled to a cell colony imaging and picking device, this approach allowed the identification of CHO cell clones secreting a therapeutic protein at high levels that were not achievable without the cell sorting procedure. Biotechnol. Bioeng. 2017;114: 1791–1802. © 2017 Wiley Periodicals, Inc. Abstract : Main mammalian DNA repair pathways, that is, non‐homologous end‐joining and homologous recombination, are not prominently used for transgene integration in CHO cell genome. Instead, this process may be mediated by DNA synthesis‐dependent microhomology‐mediated end‐joining. Inhibition of specific components of homologous recombination, and the use of DNA elements termed Matrix Attachment Region (MAR), enhances transgene integration and expression. These findings help uncover some of the mechanisms mediating DNA recombination, and they provide an approach for cell engineering to improve recombinant protein expression.